Screen Time and Early Childhood Social–Emotional Development Among Children Aged Five to Six Years - Fitria Sari; Agustien Lilawati; Mush'ab Al Umairi (Al-Qalam Institue, 2025)
Digital exposure has become a dominant part of early childhood routines and increasingly influences social–emotional development. This study aims to analyze the relationship between screen time, peer interaction, emotional regulation, and parental mediation in children aged 5–6 years. Using a qualitative case study, data were collected from six children, two teachers, and four parents through interviews, observations, and documentation. The findings show that high screen exposure triggers weakened emotional regulation, reflected in frequent tantrums, low frustration tolerance, and abrupt mood shifts. Excessive screen time also reduces peer interaction, indicated by 52% low group participation, 48% reluctance to share, and 43% preference for solitary play. Conversely, parental mediation improves social–emotional development by reinforcing cooperation, conflict resolution, and verbal expression. The novelty of this study lies in demonstrating that screen time becomes beneficial only when accompanied by active parental guidance. The results recommend collaborative screen management between schools and families to optimize children’s social–emotional growth.